Un objet bouleversant de Paul Nougé et de René Magritte : Le catalogue Samuel - Matuz, Bence (Verbum – Analecta Neolatina, 2024)
This paper intends to treat a poetic experimentation of Paul Nougé and René Magritte, entitled Catalogue Samuel (1926). Our analyses consider this artefact trough the concept surrealist of object (objet boueleversant) and the contradiction between this concept and the conditions of cultural industry. As Theodor Adorno or Pierre Bourdieu considered it, this industry subsumes the particularities of artworks and literary texts, thus the creation of surrealist objects becomes problematic. Indeed, these objects are supposed to have particularities capable to overwhelm perceptive or cognitive habitudes of the addressee, which is not possible in conditions of industrialised cultural production, because this conditions include a schematic logic classifying and generalising artworks. In this study, we try to reveal the manner in which Le catalogue Samuel, as a surrealist object, can perform its subversive and overwhelming effects even in the environment of cultural industry.